Effect of Heating Rates and Composition on the Thermal Decomposition of Nitrate Based Molten Salts. (May 2015) - Gimenez, P.; Fereres, S.
Abstract: A detailed analysis on the thermal degradation of nitrate based molten salts evaluating the influence of different impurities and heating rates in their maximum working temperature is presented. Determining the maximum operating temperature is of interest when searching for new heat transfer fluids (HTF) for high temperature solar thermal applications as it limits the thermodynamic efficiency of the power block. Thermogravimetric analysis is performed on potassium nitrate, sodium nitrate, sodium nitrite, the binary system Solar Salt, and the ternary Hitec. The kinetics of the thermal decomposition reactions are investigated through iso-conversional analysis. The effect of adding some common impurities such us NaCl and Na2 CO3 on the multi-component nitrate salts is evaluated. It was found that impurities such as Na2 CO3 can enhance the thermal stability of Hitec salt, leading to higher thermal decomposition temperatures. For solar salt, impurities such as NaCl can enhance the thermal stability of solar salt at 10K·min -1, while adding Na2 CO3 can have the opposite effect. For nitrate based molten salts used in TES and HTF systems in CSP a reduction on the purity required for the materials can present some operational advantages besides cost reduction.